Teaching and Learning Tamil as a Second Language in Sri Lanka: Special Reference to Auxiliary Verb Construction in Tamil and Sinhala Languages - Kailainathan, R. (JUICE- 2012 University of Jaffna, 2012)
The aim of this paper is to present a brief comparative and contrastive analysis of the syntactic structure of the auxiliary verbs in Tamil and Sinhala languages on a structural basis. It describes and pin-points the areas of difficulty that the speakers of these two languages have in learning each others’ languages. There are number of regional and social dialects existing in both Tamil and Sinhala. However, the Tamil data represent the author’s own dialect, the Jaffna Tamil which is a socio- regional sub-dialect of Sri Lankan Tamil. The Sinhala data represent the Colombo dialect of Sinhala. This study involves the methodology of comparative and contrastive analysis of syntactic structure of auxiliary verbs in Tamil and Sinhala, in order to establish the facts that there are similarities and dissimilarities in the two languages. To our knowledge so far, no one has attempted to embark on this selected topic. It is believed that this study of this kind would facilitate the teachers’ task of preparing teaching materials and to identify students’ difficulties in learning a second language. Further, it will reduce the students’ burden of learning a second language. This research study can be a source for implementing trilingualism at the university level. Furthermore, this study will encourage other scholars to undertake more research work in this field, so as to contribute to human knowledge and communal harmony.
Keywords: Auxiliary Verbs; Communal Harmony; Trilingualism